Introduction of a polar core into the de novo designed protein Top7. (7th March 2016) - Basanta, Benjamin; Chan, Kui K.; Barth, Patrick; King, Tiffany; Sosnick, Tobin R.; Hinshaw, James R.; Liu, Gaohua; Everett, John K.; Xiao, Rong; Montelione, Gaetano T.; Baker, David
Abstract: Design of polar interactions is a current challenge for protein design. The de novo designed protein Top7, like almost all designed proteins, has an entirely nonpolar core. Here we describe the replacing of a sizable fraction (5 residues) of this core with a designed polar hydrogen bond network. The polar core design is expressed at high levels in E. coli, has a folding free energy of 10 kcal/mol, and retains the multiphasic folding kinetics of the original Top7. The NMR structure of the design shows that conformations of three of the five residues, and the designed hydrogen bonds between them, are very close to those in the design model. The remaining two residues, which are more solvent exposed, sample a wide range of conformations in the NMR ensemble. These results show that hydrogen bond networks can be designed in protein cores, but also highlight challenges that need to be overcome when there is competition with solvent.